ENT 530 Social Media Portfolio: Mary Kay By Shuhana / Anis Shuhana Mohamad Shukri - Mohamad Shukri, Anis Shuhana (2020)
Mary Kay is an American company which was the sixth largest network marketing company in 2018. Mary Kay is based in Addison, Texas. The primary manufacturing plant is in Dallas, Texas while the second manufacturing is in Hangzhou, China. A third plant was opened in La Chaux-deFonds, Switzerland in 1997 for European market but closed later in 2003. Mary Kay was founded by Mary Kay Ash on 13 September 1963. Mary Kay International’s competitors including Amway, Chanel, Revlon, Estee Lauder, Loreal, Shiseido, Avon, Beiersdorf, Kao and Coty. Amway is Mary Kay number one competitor that was founded in 1959 in Ada, Michigan. Amway is the Personal Products industry and has 14,000 employees. The purpose of writing this report is to introduce my business, its mission and vision, description of products and price list. Mary Kay by Shuhana have more than 10 products which includes set for different ages and other skincare. This report also provides detailed information about my business which is Mary Kay by Shuhana which also one of May Kay branch through their Beauty Consultant. Mary Kay is direct-selling company that sells their products through their Beauty Consultant to ensure customer get the best product for their skin and increase their company quality. The problem statement of this business is the growth of the acne due to environmental factors, hormones, the use of facemask and UV rays. Due to this, human needs to protect their skin and treat their problems by using the correct ingredients. Mary Kay by Shuhana business’s objective is to help spread awareness of these factors that might affect our skin health and prevent from any chronic diseases such as skin cancer and bacterial infection. Mary Kay by Shuhana’s profit per month is RM800 averagely and planning to expand this business by recruiting more employees in different district and states. Overall, this report is about how this business was conducting based on hard selling copywriting guidelines, soft selling copywriting guidelines and teaser to attract more potential customer. Mary Kay by Shuhana is a health and skincare business with motto to help people know about healthy skin and healthy life. My local competitor is Kayman Beauty, AINAA Beauty, Safi, and Cosmoderms.